2010
DOI: 10.1002/etc.274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the impact of in‐ovo exposure to dicofol on avian reproduction

Abstract: To assess the possible impact of the currently used organochlorine insecticide, dicofol, on the development and reproduction of avian species, in ovo exposure experiments to its p,p' and o,p' isomers were performed using Japanese quail (Coturnix japonica) eggs. o,p'-Dicofol (0.3-100 µg/g of egg) and p,p'-dicofol (3-100 µg/g) were injected into the yolk prior to incubation and hatched chicks were raised to adulthood. In ovo treatment with o,p'-dicofol impaired the eggshell-forming ability of female quails after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…It has been reported that estrogenic compounds reduce transcription of the CYP11A1 gene in the testis not only of developing embryos but also of adults (Kamata et al, 2009a(Kamata et al, , 2009b(Kamata et al, and 2010Sakaue et al, 2002). The reduced transcription arises at very low in ovo doses of estrogens and was observed in male hatchlings exposed to o,p' -sist into adulthood (Kamata et al, 2009a(Kamata et al, , 2009b.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that estrogenic compounds reduce transcription of the CYP11A1 gene in the testis not only of developing embryos but also of adults (Kamata et al, 2009a(Kamata et al, , 2009b(Kamata et al, and 2010Sakaue et al, 2002). The reduced transcription arises at very low in ovo doses of estrogens and was observed in male hatchlings exposed to o,p' -sist into adulthood (Kamata et al, 2009a(Kamata et al, , 2009b.…”
Section: Discussionmentioning
confidence: 99%
“…PCR analyses of DNA sequences in the sex chromosomes were performed as previously reported (Kamata et al, 2010). Seven female and seven male chicks with no apparent defects were randomly selected from each treatment group at 3 days of age for -ined for gross morphological characteristics.…”
Section: Handling Of Birdsmentioning
confidence: 99%
See 1 more Smart Citation